2019
DOI: 10.1016/j.redox.2019.101222
|View full text |Cite
|
Sign up to set email alerts
|

HDL subclass proteomic analysis and functional implication of protein dynamic change during HDL maturation

Abstract: Recent clinical trials reported that increasing high-density lipoprotein-cholesterol (HDL-C) levels does not improve cardiovascular outcomes. We hypothesize that HDL proteome dynamics determine HDL cardioprotective functions. In this study, we characterized proteome profiles in HDL subclasses and established their functional connection. Mouse plasma was fractionized by fast protein liquid chromatography, examined for protein, cholesterial, phospholipid and trigliceride content. Small, medium and large (S/M/L)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 52 publications
2
43
0
Order By: Relevance
“…43 The different associations among lipoprotein subparticle sizes support the notion that the composition of lipoproteins may be important, and this can affect their functional role. 44 Further research into the composition of HDL and VLDL subparticles among different diseases is warranted to understand the meaning of these associations. 12 Decreased MUFA, SFA, and TotFA levels were identified in AMD patients compared with control participants in the current metabolomics study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…43 The different associations among lipoprotein subparticle sizes support the notion that the composition of lipoproteins may be important, and this can affect their functional role. 44 Further research into the composition of HDL and VLDL subparticles among different diseases is warranted to understand the meaning of these associations. 12 Decreased MUFA, SFA, and TotFA levels were identified in AMD patients compared with control participants in the current metabolomics study.…”
Section: Discussionmentioning
confidence: 99%
“…A potential interaction between HDL and the complement system was shown in proteomic studies that demonstrated that HDL lipoprotein particles contain various complement components. 44 Notably, large HDL subparticles were shown to contain complement factor H (CFH), whereas small HDL and medium HDL subparticles did not. Although Zhang et al 44 propose that the increased CFH concentration would provide large HDL subparticles with anti-inflammatory properties, our study suggested the opposite: increased large HDL levels were associated with increased systemic complement activity.…”
Section: Discussionmentioning
confidence: 99%
“…The direct relationship between PON1 and oxidative stress is an indicator that PON1 plays a role in general antioxidative protection. In a study by Zhang and colleagues, HDL subclass proteomics confirmed that PON1 is situated within medium/large HDL particles where it is responsible for its antioxidative properties …”
Section: Pon1 and Diseases Connected With Atherosclerosis Developmentmentioning
confidence: 95%
“…In a study by Zhang and colleagues, HDL subclass proteomics confirmed that PON1 is situated within medium/large HDL particles where it is responsible for its antioxidative properties. 67 After our PON1/CVD-related work, we continued with studies focusing on acute ischemia and stroke. This is another complication within the vascular system with a defective atherosclerotic background.…”
Section: Pon1 and Vascular Diseasesmentioning
confidence: 99%
“…This effect coincided with changes in TG levels in VLDL subclasses, which was also observed with sitagliptin treatment. Although the atherogenicity of HDL subclasses are still a matter of controversy, the changes observed here in HDL subclasses may play a functional role [20].…”
Section: Discussionmentioning
confidence: 80%